DIVERSIFIKASI PENGOLAHAN UBI KAYU DALAM MENINGKATKAN KETAHANAN PANGAN DI SULAWESI BARAT: Diversification of Cassave Processing in Improving Food Security in West Sulawesi - Ketut Indrayana; Marthen P Sirappa; Muh Ricky (Program Studi Agroteknologi Fakultas Pertanian, Peternakan, dan Kehutanan Universitas Muslim Maros, 2018)
Rice is the staple food of Indonesian people. Procurement of rice in the future will be difficult considering the population continues to grow, irrigated rice field area has undergone many functions for non-agricultural purposes, and the productivity level of paddy fields has experienced saturation and tends to decrease and changes in consumption from non-rice to rice in some areas. The consumption pattern that only relies on one type of staple food, such as rice, is one of the causes of the food security problem. An effort to anticipate this problem is through food diversification by consuming non-rice local food. Non-rice food commodities include cassava, corn, sorghum, beans and sago. Cassava has the potential to be developed as non-rice food substitute. West Sulawesi has the opportunity to utilize cassava as a non-rice food ingredient through food diversification to support food security. However, processed commodities are still limited in the form of semi-finished materials (opaque). The efforts to increase the consumption of cassava can be done through diversification of processed cassava products such as cassava flour and processed various cakes and snacks such as various flavored opaque. By processing of cassava, it is expected to be able to support food security in West Sulawesi